Hrmmmm let's see here...
the fourth statement
Answer:
15
÷
2
x
Step-by-step explanation:
Since it's a expression, no answer would be needed, so you just write the way the phrase says. Let's say, "What's the quotient of three and the six times x" That would be 3÷6x
F(x) = 3x^2+6x-2
= 3(x^2+2x-2/3)
= 3(x^2 +2x + 1 - 1 - 2/3)
= 3((x+1)^2 - 1 - 2/3)
= 3((x+1)^2 -5/3))
= 3(x+1)^2 - 5
So our function is in the form:
f(x) = 3(x+1)^2 - 5
where a = 3, h = -1, k = -5
Answer:
(-2, -3)
(3, 12)
Step-by-step explanation:
To solve this, we're gonna get rid of the y's with substitution
x² + 2x - 3 = 3x + 3
Let's make this equation equal to zero
Subtract 3 from both sides
x² + 2x - 3 = 3x + 3
- 3 - 3
x² + 2x - 6 = 3x
Subtract 3x from both sides
x² + 2x - 6 = 3x
- 3x - 3x
x² - x - 6 = 0
Factor the equation
(x - 3)(x + 2) = 0
This means x can be -2 or 3
Let's solve it with -2 first, plug the new x in y = 3x + 3
y = 3(-2) + 3
y = -6 + 3 = -3
Do the same for x = 3
y = 3(3) + 3
y = 9 + 3 = 12